EKSEKUSI JAMINAN DALAM PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH - Awaliyah, Robi’ah; Mujib, Abdul (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
This article is a library research with research data sources sourced from primary and secondary sources. The primary data sources in this study are the Qur'an, hadith, laws, and fatwa. While the secondary sources are books, journals, theses, websites and others. The data analysis method used is a qualitative-descriptive analysis method. One of the financing contracts used by prospective customers to Islamic banks in meeting customer needs is murabahah. Murabahah is a term in Islamic jurisprudence which means a certain form of buying and selling when the seller states the cost of acquiring the goods, including the price of the goods and other costs incurred to obtain the goods, and the desired level of profit (margin). In supporting the continuity of the murabahah contract, Islamic banks need guarantees to minimize risk, for customers who break their promises. Efforts to resolve customer problems in murabahah financing are carried out in 2 (two) stages, namely rescue efforts and settlement efforts. The final solution if the customer has not been able to pay off the debt is by executing the collateral, either by taking over the collateral by the bank, selling it voluntarily or selling the collateral through auction.Keywords: Murabaha, Guarantee, execution